Clinical and Sonographic Changes of Parotid Gland in Patients with Type I and Type II Diabetes Mellitus and Its Effect on Physical Properties of Saliva - Al-Ubaidy, Rawaa A. A.; Rasheed, Rafil Hameed; Al-Sabbagh, Ahmed A. A. (Journal of Baghdad College of Dentistry, 2016)
Background: Sialosis described as a specific consequence of diabetes. In diabetic sialosis, the increased volume of the glands is due to the infiltration of adipose in the parenchyma. The B-scan ultrasonography is a generally accepted tool for determining parotid gland enlargement. Oral health is, to a greater extent, dependent on quality and quantity of saliva, both of which may be altered in diabetics. This study was established to detect the enlargement of parotid gland in diabetic patient and study the changes in physical properties of saliva and its relation with the salivary gland enlargement. Subjects, Materials and Methods: A cross-sectional study with highly specified criteria with ages ranged (20-65) years, male and female subjects who attending Al-Yarmouk teaching hospital (Al-Yarmouk center for Diabetes). Parotid gland was measured by using B-mode ultrasonography with a high frequency (6-9MHz). Physical properties of saliva were measured namely: flow rate, pH, and viscosity. Results: The statistical analysis showed that: The right-left mean difference in length, width, depth and volume ultrasonography measurements of parotid gland among diabetic study group, revealed non statistically significant difference, similar result was obtained among control group. The effect of Diabetes mellitus is marked on the parotid gland measurements as the disease progresses and the HbA1c increase. Physical properties of saliva give obvious decrease in flow rate and pH in diabetic patient while the viscosity was increased in diabetic rather than normal. Conclusion: This study concludes that there is positive correlation between the progressions of disease and salivary gland measurements. On the other hand, the present article shows that there is negative association between flow rate, pH, and viscosity in comparison with salivary gland measurements